The Penerapan Firewall Untuk Keamanan Jaringan Pada SMKN 3 Kota Bengkulu - Pangeran Al Amin; Khairil Khairil; Abdussalam Al Akbar (Jurnal Media Infotama, 2026)
The use of computer networks at SMK Negeri 3 Kota Bengkulu increases the need for security against threats such as illegal access and DoS/DDoS attacks. This study implements a Mikrotik firewall using Filter Rules, Raw Rules, Mangle Rules, and DDoS limits using the Security Life Cycle (SLC) method.Test results show that Filter Rules are effective in blocking illegal access, Raw Rules are efficient in handling volumetric attacks because they work before connection tracking, and Mangle Rules are useful for traffic management. The application of DDoS limits has been proven to reduce the number of excessive connections so that the network remains stable.This study proves that the Mikrotik firewall can enhance school network security and can serve as a reference for implementing more comprehensive security policies